Pain-induced depression in the elderly: Validation of psychometric properties of the Brazilian version of the “Geriatric Emotional Assessment of Pain” - GEAP-b - Almeida,Carla Bezerra Lopes (2017)
Summary Objective: In order to introduce an instrument within our midst that allows a comprehensive clinical evaluation of pain-induced depression in the elderly, we proposed the translation, cross-cultural adaptation into Brazilian Portuguese, and study of the psychometric properties of the “Geriatric Psychosocial Assessment of Pain-induced Depression” (GEAP) scale. This instrument was especially developed for the screening of depression associated with chronic pain in the elderly. Method: We performed translation and cross-cultural adaptation of the GEAP scale, whose psychometric properties were analyzed in a sample of 48 elderly individuals. Sociodemographic data and information related to chronic pain were ascertained, as well as those related to depression. The GEAP-b scale was applied at three different times on the same day by two different interviewers (I1 and I2), and after 15 days by one of those interviewers (I3). Results: The GEAP-b proved to be an easy-to-apply instrument with a high internal consistency value, according to the Cronbach’s alpha coefficient (0.835). The reproducibility of the instrument was optimal, achieving intraclass correlations of 98.5 and 92% for interobserver and intraobserver, respectively. There was “considerable” agreement (between 0.419 and 1.0) for each GEAP-b item, except for item 19, according to the kappa statistic. As for the validity of the GEAP-b criterion, positive and statistically significant correlations were obtained for pain, according to GPM-p (r=49.5%, p<0.001), and depression, according to GDS (r=59%, p<0.001), both values being considered regular (between 40-60%). Conclusion: The GEAP-b scale has proven to be reliable and valid in the screening of pain-related depression in the elderly.